INDONESIAN LANGUAGE TEACHING MATERIAL DESIGN SKILLS OF JUNIOR HIGH SCHOOL TEACHERS IN EAST LOMBOK WITHIN THE DEEP LEARNING PARADIGM - Ahsanul Aini; Khirjan Nahdi; Roni Amrulloh (Antis Publisher, 2026)
Objective: This study aims to describe the skills of Indonesian language teachers at the junior high school and Islamic junior high school levels in East Lombok in designing teaching materials aligned with the deep learning paradigm. Deep learning encompasses the dimensions of learning principles—meaningful, mindful, and joyful—pedagogical frameworks, reading literacy, verbal communication, learning cycles, and twenty-first-century competencies. Method: Research data were triangulated through three primary sources: questionnaires completed by 22 teachers, individual interviews, and a review of 17 teaching module documents. The data were analyzed using a sequential explanatory mixed-methods design to reveal the gap between teachers’ self-perceptions and their actual implementation in instructional documents. The research method combined Likert-scale score analysis and qualitative thematic analysis based on an interactive model. Results: The results showed an average questionnaire score of 4.04, categorized as Good. The Deep Learning Principles dimension obtained the highest score of 4.20, although its implementation was the most uneven according to the document analysis. Interview data revealed a readiness gap between teachers who had and had not participated in formal training. The document review showed that critical literary literacy was absent from most modules, while digital integration remained consumptive. Teachers’ teaching-material design skills were perceived as good, but their implementation was constrained by conceptual gaps and institutional structural factors, particularly the policies of pesantren-based schools. Novelty: The urgency of this study lies in the gap between curriculum policies promoting deep learning and the limited empirical evidence regarding the readiness of language teachers in rural-coastal areas to translate these principles into concrete teaching modules, particularly in pesantren-based schools with structural limitations.